Animism of the Nilotics and Discourses of Islamic Fundamentalism in Sudan. - Maluil Jok, Kuel (SIdestone Press, 2011)
This book provides a comprehensive analysis of Animism as a religion and a culture of the Nilotic peoples of the Upper River Nile in modern 'Southern Sudan'. It gives an account of how the Animistic ritual performances of the divine chief-priests are strategies in conflict management and resolution. For centuries, the Nilotic peoples have been resisting changes to new religious identities and conservatively remained Animists. Their current interactions with the external world, however, have transformed their religious identities. At present, the Nilotics are Animist-Christians or Animist-Musli.